Tipos de cubiertas y su influencia en las características agronómicas y rendimiento de Lactuca sativa L., lechuga, en Zungarococha - Loreto.2023 - Caballero Viena, Lord Hernan (2023)
The study was carried out in a clay loam soil of the Zungarococha Estate with UTM coordinates 9576247 North and 682167 South, where the responses of the characteristics and performance of lettuce to protection with two types of covers (raschel mesh and palm leaves) and without cover were appreciated. 08 variables were appreciated: height, width, number of leaves, plant weight, length, root and stem weight, highlighting the treatment with palm leaves through the Tukey Test in the Statistical Design of the DBCA, with plant weight of 92 g and 13,800 Kg/ha with an economic income of S /20,670, recommending its use because it allows to have a better ventilation under it that favors the development of the plants under our local climatic conditions and saving the cost of covers.